2020
DOI: 10.1021/acsearthspacechem.0c00139
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Fractionation during Condensation and Evaporation during Planet Formation Processes

Abstract: During the early stages of a protoplanetary disk, it is expected that the temperatures reached in the disk will lead to total or partial vaporization of dust, followed by condensation upon cooling. Similarly, chondrule forming events or giant impacts followed by magma oceans can also produce partial evaporation. Thus, moderately volatile elements can be mobilized during these thermal events, thereby leading to characteristic isotope signatures that can be used to decipher the conditions of elemental fractionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 96 publications
(303 reference statements)
2
21
0
Order By: Relevance
“…This model shares similarities with those applied to closed-system condensation/evaporation and chondrule formation ( 22 24 , 26 , 27 ). The chemical depletions and isotopic fractionations of the REEs evaporated depend on the heating rate and duration of the evaporation episode.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This model shares similarities with those applied to closed-system condensation/evaporation and chondrule formation ( 22 24 , 26 , 27 ). The chemical depletions and isotopic fractionations of the REEs evaporated depend on the heating rate and duration of the evaporation episode.…”
Section: Discussionmentioning
confidence: 87%
“…The value of T c ,0 has little influence on the model result provided that it is high enough that all REEs are fully evaporated at the beginning of the calculation. In our simulations, we adopt a value of 1700 K. Condensation happens in a closed system [also see ( 22 , 26 )] until a time or temperature at which the vapor is dissipated and the remaining least refractory REEs are lost. We define the time scale of the condensation event as the time span between 5% condensation of highly refractory REE (Dy) and the time of gas dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…Kadlag et al (2019) reported a e 54 Cr value (1.79 ± 0.20) for Ivuna, which is higher than that reported in other literature (Schiller et al, 2014;Shukolyukov and Lugmair, 2006;Van Kooten et al, 2016), while Williams et al (2020) reported a lower e 54 Cr value of 1.30 ± 0.09. As for e 53 Cr values, Shukolyukov (Bourdon and Fitoussi, 2020;Qin et al, 2010;Shukolyukov and Lugmair, 2006;Trinquier et al, 2006Trinquier et al, , 2008a]. Despite some inconsistency between the various studies, we list and consider all published data in Table 3.…”
Section: Comparison Of Cr Isotope Data For Chondrites With Literaturementioning
confidence: 99%
“…The mass-independent Cr isotope compositions of meteorites are traditionally measured by thermal ionization mass spectrometry (TIMS) (Birck and Alle `gre, 1988;Lugmair and Shukolyukov, 1998;Qin et al, 2010;Shukolyukov and Lugmair, 2006;Trinquier et al, 2007;Trinquier et al, 2008a). However, it appears that there are small residual mass-dependent fractionations that cannot be corrected for, which are evident in the correlation of e 53 Cr and e 54 Cr for multiple measurements of standards with a slope of $2 (Bourdon and Fitoussi, 2020;Qin et al, 2010;Trinquier et al, 2006). It has been suggested that such residual mass-dependent isotopic fractionations could potentially arise from isotopic fractionation between different oxidized Cr gas species during evaporation from the filaments during TIMS analysis (Bourdon and Fitoussi, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation